Microzonation of Landslide Potential Areas Using the Microtremor Method in the North Bengkulu - Lebong Regency - Ardika Pratama Panjaitan; Ronni Saragih; Anggiat Hutahuruk; Suhendra Suhendra (Jurnal Fisika Flux: Jurnal Ilmiah Fisika FMIPA Universitas Lambung Mangkurat, 2023)
The road crosses the North Bengkulu district to the Lebong district is one of the areas where landslides frequently occur in Bengkulu province. The occurrence of landslides can be caused by high rainfall, steep hillsides, high levels of soil vulnerability, and others. This study aims to map landslide-prone areas build on indicators of the natural frequency value (f0), the amplification value (A0), and the soil vulnerability value (Kg). Measurements from this study used the PASI Mod Gemini 2 Sn-1405 seismometer for ± 30 minutes at 25 measurement points. Geopsy software is used for microtremor data processing to obtain the H/V curve. The results obtained are dominant frequency values between 1.3 – 7.6 Hz, amplification factor values between 1.6 – 6.93, and seismic vulnerability index values 0,5 – 8. After getting the values of these parameters, a distribution map is made based on the values of each parameter, making distribution map using surfer software by merging the values of each parameter and the coordinates of the research location points. Based on the values of these parameters it can be concluded that the areas that have the potential for landslides are in the area of points T1, T6, and T25.